Mechanisms of change in gel water-holding capacity of myofibrillar proteins affected by lipid oxidation: The role of protein unfolding and cross-linking. (15th May 2021) - Jiang, Yi; Li, Dahu; Tu, Juncai; Zhong, Yujie; Zhang, Dong; Wang, Zhaoming; Tao, Xiaoqi
Highlights: Lipid oxidation resulted in both unfolding and cross-linking of myofibrillar protein. Protein unfolding and cross-linking jointly determined gel water holding capacity. Moderate oxidation favored gel water holding capacity, while excessive oxidation not. Abstract: This work explored the effects of protein unfolding and cross-linking induced by lipid oxidation (linoleic acid, OLA) on the gel water-holding capacity (WHC) of beef myofibrillar proteins (MP). Medium concentration of OLA (≤6 mM) caused the increase of gel WHC from 55.2% to 65.1%, while relative high OLA concentration (>6 mM) decreased the gel WHC. When the OLA concentrations increased from 0 to 10 mM, the population of immobile water of gel decreased from 92.91% to 78.97%, whereas that of free water increased from 6.13% to 19.80%, suggesting that OLA treatment regardless concentration was harmful for gel WHC. However, medium OLA concentrations (≤6 mM) caused the shifting of α-helixes to β-sheets in MP gel, exerting positive effect on gel WHC. Protein unfolding and cross-linking jointly determined the increased gel WHC at moderate oxidative modification. Additionally, the protein aggregation at high OLA concentration resulted in decreased gel WHC.